REPOSITORI DATA NASIONAL: TANTANGAN BARU PENGEMBANGAN KOLEKSI PERPUSTAKAAN - Titiek Kismiyati (Perpustakaan Nasional, 2020)
Data has become one of the important things in research. Data as a library collection will make the library more complete. That is why more and more institutions want research results not only in the form of research reports, but also in the form of usable datasets. Data that is managed by the library can be reused by other researchers to allow for further research.The various data that have been collected and processed will become a form of